Simple method for detection of the self-heating signature - Mori, C. A. B. (2017)
This paper reports a simple method for detection of the self-heating effect through a special signature, without the need of specific structures or high frequency systems, even in devices presenting positive output conductances. In order to develop this method, simple numerical models were employed, and later verified through experimental observation with pFinFET devices.